Analysis of the Introduction to the School Field in relation to Curricular, Co-curricular and Extra-curricular Activities at SMP Negeri 1 Wuluhan. - Azizah, Nurlaily; Shofiyani, Defi; Anggita, Febrianti Dwi; Kumalasari, Arista Eka; Mahardika, I Ketut (Peneliti.net, 2024)
Introduction to the School Field is an observation or observation activity carried out by students in the school environment. The aim of this research is to analyze the results of observations or observations made in the school environment in relation to curricular, co-curricular and extra-curricular activities at SMP Negeri 1 Wuluhan. The method used in the analysis of Introduction to the Schooling Environment uses school observation methods, interviews with several teachers, and document analysis from the results of observations and interviews. The results of this research show that at SMP Negeri 1 Wuluhan there are various curricular, co-curricular and extra-curricular activities. Curricular activities at SMP Negeri 1 Wuluhan include study guidance and olympiad guidance. Meanwhile, co-curricular activities include school orientation periods and study tours, but these study tour activities have been stopped since Covid-19 hit. And for extracurricular activities, there are 9 extracurricular activities at SMP Negeri 1 Wuluhan with a predetermined schedule and selected supervisors.